CFD investigation on heat transfer improvement of subcooled flow boiling in a vertical upflow minichannel with straight and enhanced geometrical structure - Amal Igaadi; Rachid El Amraoui; Hicham El Mghari (e-Prime: Advances in Electrical Engineering, Electronics and Energy, 2023)
This paper presents the effects of minichannel geometrical configuration on flow structures, hydrodynamics, and heat transfer behavior of the subcooled flow boiling process in a cooling system with high heat flux. The two-dimensional numerical simulations are quantitatively conducted for dielectric fluid FC-72 as a working fluid in two different configurations (straight and periodic constriction-expansion) of a minichannel mounted vertically at three inlet temperatures (285.35, 304.54, and 325.35 K) at constant mass flux (836.64 kg/m2s) and input heat flux (191,553 W/m2). The predicted results are in excellent agreement with the published experimental data, which proves the efficiency of the present numerical model. In both configurations, the heat transfer coefficient increases with an increase in the inlet temperature. The results show that the periodic constriction-expansion design significantly improves the heat transfer performances of subcooled flow boiling by 21.77–36.9% for Tin = 285.35–325.35 K because the periodic constriction-expansion configuration offers good mixing between layers.